A case of severe mucosal changes in a patient with Mycoplasma pneumoniae pneumonia - Morawski, Marcin; Kaleta, Magdalena; Mroczka, Maria; Gawlewicz-Mroczka, Agnieszka (Alergologia Polska - Polish Journal of Allergology, 2025)
This case report describes a 45-year-old female, with diagnosis of Mycoplasma pneumoniae pneumonia treated with clarithromycin. The patient developed severe mucosal changes, including crusting of the lips, conjunctivitis and extensive oral erosions, prompting suspicion of Stevens-Johnson syndrome. The patient’s condition was managed with a combination of antibiotics, corticosteroids, and intravenous immunoglobulins, resulting in gradual clinical improvement. This case highlights the challenges in differentiating between drug-induced hypersensitivity and infectious mucocutaneous eruptions, such as reactive infectious mucocutaneous eruption caused by Mycoplasma pneumoniae. Given the rising incidence of Mycoplasma pneumoniae infections, it is essential to consider both infectious and drug-induced causes of severe mucocutaneous reactions.